Actuator
The actuator design combines a high Young's modulus skeletal structure with an isotropic volume changing part to achieve both high output force and large deformability, addressing the limitations of conventional actuators.
Patent Information
- Application Number
- JP2021017563
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-03-31
- Filing Date
- 2021-02-05
- Publication Date
- 2024-12-18
- Estimated Expiration
- 2041-02-05
AI Technical Summary
Conventional actuators lack materials that can achieve both high output force and large deformability, as materials with high Young's modulus typically have low strain, while materials with large strain have low Young's modulus.
The actuator design incorporates a skeletal structure part with a higher Young's modulus surrounding a volume changing part, where the volume changing part expands isotropically when external energy is input, causing the skeletal structure to deform anisotropically, allowing for both high Young's modulus and large strain.
This design increases the actuator's output by enabling both high Young's modulus and large strain, resulting in enhanced force generation and deformation capabilities.
Smart Images

Figure 0007602228000004 
Figure 0007602228000005 
Figure 0007602228000006
Abstract
Description
[Technical field]
[0001] The present invention relates to an actuator. [Background technology]
[0002] Patent Document 1 and Non-Patent Document 1 disclose actuators using polymer fiber materials as actuators using materials that convert external energy input from the outside other than mechanical energy into mechanical energy and output a force to the outside. This actuator utilizes the operation of the polymer fiber material caused by the input of thermal energy. The actuator disclosed in Patent Document 1 uses fiber materials of PA6 and PA66. The actuator disclosed in Non-Patent Document 1 uses fiber material of PA11. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] U.S. Patent No. 9,784,249 [Non-patent literature]
[0004] [Non-Patent Document 1] Proceedings of the 2017 Spring Meeting of the Japan Society for Precision Engineering, pages 171 and 172, Japan Society for Precision Engineering Summary of the Invention [Problem to be solved by the invention]
[0005] However, there is a demand for actuators with higher output than conventional actuators. In order to increase the output of an actuator, that is, to increase the external force and to make the actuator material deform more, it is necessary to use a material that has both the property of large distortion caused by the input of external energy and the property of a high Young's modulus.
[0006] In view of the above, an object of the present invention is to provide an actuator capable of achieving high output. [Means for solving the problem]
[0007] In order to achieve the above object, according to the invention described in claim 1, The actuator has a skeletal structure portion (12, 21, 22, 42) that forms a skeletal structure surrounding a housing portion (11, 24, 41), and a volume change portion (13, 23, 43) that is housed in the housing portion, The volume change portion increases in volume when external energy other than mechanical energy is input from the outside, The skeletal structure has a higher Young's modulus than the volume change portion, When external energy is input to the volume change portion, the volume of the volume change portion increases, and the skeletal structure portion deforms so that the storage portion contracts in one direction (D2, D11) and expands in the other direction (D3, D12) due to the increase in the volume of the volume change portion. death, The actuator is made of a fiber material, and outputs a tensile force in the fiber axis direction (D1, D11) of the fiber material by inputting external energy. The one direction is a direction along the fiber axis direction, The shape of the storage portion is anisotropic, in which the maximum width (LD2) of the storage portion in one direction is greater than the maximum width (LD3) of the storage portion in the other direction; The fiber material is at least composed of a polymer material having a plurality of crystalline portions (21) in which polymer chains are regularly arranged, a plurality of tie molecules (22) in which the polymer chains extend so as to connect each of the plurality of crystalline portions to each other, and a plurality of amorphous portions (23) in which the polymer chains are irregularly arranged; The plurality of tie molecules includes a plurality of first tie molecules (221) extending in a first direction (D2) and a plurality of second tie molecules (222) extending in the first direction, each of the plurality of first tie molecules and each of the plurality of second tie molecules are alternately arranged in a second direction perpendicular to the first direction; A first space (B1) is formed between one second tie molecule of the plurality of second tie molecules and one first tie molecule (221a) located adjacent to one second tie molecule of the plurality of first tie molecules on one side in the second direction; A second space (B2) is formed between one second tie molecule and one first tie molecule (221b) located adjacent to one of the plurality of first tie molecules on the other side in the second direction with respect to the one second tie molecule, the plurality of crystal portions include a plurality of first crystal portions (21a) provided in the first space and a plurality of second crystal portions (21b) provided in the second space; the plurality of amorphous portions include a plurality of first amorphous portions (23a) provided in the first space and a plurality of second amorphous portions (23b) provided in the second space; In the first space, the first crystal portions and the first amorphous portions are alternately provided in a first direction, In the second space, the second crystal portions and the second amorphous portions are alternately provided in the first direction, one first crystal portion of the plurality of first crystal portions in the first space faces one second amorphous portion of the plurality of second amorphous portions in the second space in the second direction, and one second crystal portion of the plurality of second crystal portions in the second space faces one first amorphous portion of the plurality of first amorphous portions in the first space in the second direction; a length in the first direction of each of the plurality of amorphous portions is longer than a length in the first direction of each of the plurality of crystalline portions; the volume change portion is one amorphous portion among the plurality of amorphous portions, The framework structure portion is a portion that surrounds the plurality of crystalline portions and one amorphous portion of the plurality of tie molecules, The density of polymeric materials is 0 g / cm 3 Larger, 1.03g / cm 3 Less than. According to the invention described in claim 4, the actuator comprises: a skeletal structure portion (12, 21, 22, 42) that forms a skeletal structure surrounding the storage portion (11, 24, 41); A volume change portion (13, 23, 43) accommodated in the accommodation portion, The volume change portion increases in volume when external energy other than mechanical energy is input from the outside, The skeletal structure has a higher Young's modulus than the volume change portion, When external energy is input to the volume change section, the volume of the volume change section increases, and the increase in the volume of the volume change section causes the storage section to contract in one direction (D2, D11) and the skeletal structure section to deform so that the storage section expands in another direction (D3, D12) different from the one direction, The actuator is made of a fiber material, and outputs a tensile force in the fiber axis direction (D1, D11) of the fiber material by inputting external energy. The one direction is a direction along the fiber axis direction, the skeletal structure is a braided sleeve (42) having a cylindrical structure in which one or more fibers are combined to surround the housing, and which is more easily stretchable in a width direction (D12) perpendicular to the fiber axis direction than in the fiber axis direction; the volume change portion is a solid polymer material (43) that expands isotropically when thermal energy is input as external energy when there is no constraint on its external shape; When thermal energy is input into the polymer material, the volume of the polymer material increases, and the volume of the volume change portion increases, causing the braided sleeve to deform so that the contained portion shrinks in the fiber axis direction and the contained portion expands in the width direction. One or more fibers that make up the braided sleeve generate heat when an electric current is passed through them, The textile material has nodes (44) that restrict the braided sleeve from expanding in the width direction. The nodes are narrower than the outer shape of the braided sleeve, and are fixed at predetermined intervals around the braided sleeve in a circular or spiral shape.
[0008] This allows the Young's modulus of the actuator to be increased, compared to when the actuator is made of only the material that makes up the volume change section.
[0009] According to this, when external energy is input to the volume changing portion, the volume of the volume changing portion increases, and the increase in the volume of the volume changing portion causes the skeletal structure to deform so that the accommodation portion contracts in one direction and expands in the other direction, thereby making it possible to increase the strain of the actuator generated when external energy is input, compared to when the actuator is made of only the material that constitutes the skeletal structure and when the actuator is made of only the material that constitutes the volume changing portion.
[0010] In this way, it is possible to provide the actuator with both a property of large distortion caused by the input of external energy and a property of high Young's modulus, thereby enabling the actuator to have high output.
[0011] The reference symbols in parentheses attached to each component indicate an example of the correspondence between the component and specific components described in the embodiments described below. [Brief description of the drawings]
[0012] [Figure 1] FIG. 2 is a schematic diagram of an actuator according to the first embodiment. [Diagram 2] FIG. 2 is a diagram showing a model of a unit structure of the actuator in FIG. [Diagram 3] FIG. 1 shows a model of the bulk structure of a polyamide-based fiber material. [Figure 4] FIG. 4 is an enlarged view of a portion IV in FIG. 3, showing a model of a unit structure of a polyamide-based fiber material. [Diagram 5] FIG. 2 is a diagram showing a model of a unit structure of a polyamide-based fiber material, illustrating a change in shape of the unit structure due to a change in volume of an amorphous portion. [Figure 6] FIG. 2 is a diagram showing the relationship between the magnitude of tension applied to a PA6 fiber material and the linear expansion coefficient of the PA6 fiber material. [Figure 7] FIG. 2 is a diagram showing the Young's modulus of the crystalline part and the amorphous part of PA6, and the Young's modulus of a fiber material of PA6. [Figure 8] FIG. 1 is a diagram showing a model of the unit structure of a polyamide-based fiber material. [Figure 9] FIG. 1 is a diagram showing the relationship between the crystallinity and the linear expansion coefficient in PA6. [Figure 10] FIG. 1 is a diagram showing calculation results and actual measured values of the linear expansion coefficient of PA6 fiber material. [Figure 11] 1 is a flowchart showing a method for producing a PA12 fiber material. [Figure 12] FIG. 1 is a schematic diagram showing a production apparatus for PA12 fiber material. [Figure 13] FIG. 1 is a diagram showing the measurement results of the shrinkage rate of each of PA12, PA6, and PA66 fiber materials produced at the same draw ratio. [Figure 14] 13 is a schematic diagram of an actuator having nodes in a second embodiment. FIG. [Figure 15] FIG. 11 is a schematic diagram of an actuator having no nodes in the second embodiment. [Figure 16]FIG. 11 is a diagram showing the relationship between the expansion rate of a polymer material and the contraction rate of an actuator having nodes and an actuator having no nodes in the second embodiment. [Figure 17] 5A to 5C are diagrams for explaining a manufacturing method of the actuator in the embodiment. [Figure 18] 18 is a diagram illustrating the method of manufacturing the actuator subsequent to FIG. 17. FIG. [Figure 19] 19 is a diagram illustrating the method of manufacturing the actuator subsequent to FIG. 18. FIG. [Figure 20] 1 is a photograph of an actuator before heating in an example. [Figure 21] 1 is a photograph of an actuator after heating in an example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] Hereinafter, embodiments of the present invention will be described with reference to the drawings. In the following embodiments, parts that are the same or equivalent to each other will be denoted by the same reference numerals.
[0014] (First embodiment) The actuator 1 shown in Fig. 1 uses a material that converts external energy other than mechanical energy input from the outside into mechanical energy and outputs it. Specifically, this actuator 1 uses a fiber material, and contracts in the fiber axis direction D1 of the fiber material when external energy is input. This outputs a tensile force in the fiber axis direction D1 to the outside. The actuator 1 shown in Fig. 1 is linear, but may be coiled to increase the stroke.
[0015] Next, the material design of the actuator 1 discovered by the present inventors will be described.
[0016] The actuator 1 is composed of a material having a plurality of unit structures 10. FIG. 2 is a model diagram showing the change in the unit structures before and after input. The left side of FIG. 2 shows the state before input. The right side of FIG. 2 shows the state after input. As shown on the left side of FIG. 2, the unit structure 10 includes a skeletal structure portion 12 that forms a skeletal structure surrounding one storage portion 11, and a volume change portion 13 that is stored in the one storage portion 11. That is, the actuator 1 has a skeletal structure portion 12 and a volume change portion 13.
[0017] The skeletal structure 12 is a part that mainly contributes to the strength of the material, and is a structural part that forms the skeleton of the material. The Young's modulus of the skeletal structure 12 is higher than the Young's modulus of the volume change part 13. The skeletal structure 12 has a three-dimensional structure. The skeletal structure 12 extends in a pantograph shape. A part of the extension direction of the skeletal structure 12 is inclined in a direction perpendicular to that direction.
[0018] The skeletal structure 12 is preferably a hollow shell structure, i.e., a sealed structure that completely covers the accommodation section 11. However, the skeletal structure 12 does not have to be a sealed structure. When the volume of the volume changeable section 13 accommodated in the accommodation section 11 increases, the greater the force that the skeletal structure 12 receives, the more a part of the skeletal structure 12 is pushed by the force and deforms so as to tilt, thereby making it possible to increase the amount of deformation of the skeletal structure 12, which will be described later.
[0019] In addition, in the unit structure, the portions constituting the skeletal structure 12 are preferably chemically bonded to each other and are continuous, but may not be chemically bonded. In the material constituting the actuator 1, the multiple skeletal structure 12 are three-dimensionally connected to each other. Each of the multiple skeletal structure 12 is preferably chemically bonded to each other and are continuous, but may not be chemically bonded.
[0020] The volume change section 13 is surrounded by the skeletal structure section 12. The volume of the volume change section 13 increases when external energy other than mechanical energy is input from the outside. Examples of external energy include thermal energy, electrical energy, chemical energy, and light energy. For example, the input of thermal energy means that the temperature of the actuator is increased to a high temperature. When comparing the amount of volume increase due to the input of external energy under the same conditions, the amount of volume increase of the volume change section 13 is greater than the amount of volume increase of the skeletal structure section 12.
[0021] The shape of the storage section 11 is anisotropic in the direction of the maximum width of the storage section 11 in each direction, i.e., a shape other than a sphere. That is, the shape of the storage section 11 is anisotropic in which the maximum width LD2 of the storage section 11 in one direction is longer than the maximum width LD3 of the storage section 11 in another direction different from the one direction. For example, as shown on the left side of FIG. 2, when the cross-sectional shape of the storage section 11 is an oblong spheroid, the longitudinal direction D2 corresponds to one direction, and the short direction D3 perpendicular to the longitudinal direction corresponds to the other direction. The longitudinal direction D2 is the direction along the fiber axis direction D1 in FIG. 1.
[0022] As shown on the left side of FIG. 2, in the state before the external energy is input, the volume changeable portion 13 is accommodated in the accommodation portion 11 of the skeletal structure portion 12, and the accommodation portion 11 has an anisotropic shape other than a sphere. The volume changeable portion 13 is arranged in advance so that the direction in which it expands when energy is input is the short-side direction D3. When external energy is input to the skeletal structure portion 12 and the volume changeable portion 13, the volume changeable portion 13 expands in the short-side direction D3. The volume changeable portion 13 has a larger volume change due to the input of the external energy than the skeletal structure portion 12. Therefore, the skeletal structure portion 12 is pushed in the short-side direction D3 to expand, while contracting in the longitudinal direction D2.
[0023] Therefore, as shown on the right side of FIG. 2, the increase in the volume of the volume change portion 13 causes the skeletal structure 12 to deform in a direction in which the shape of the storage portion 11 approaches a sphere. That is, the increase in the volume of the volume change portion 13 causes the storage portion 11 to contract in the longitudinal direction D2 and the skeletal structure 12 to deform so that the storage portion 11 expands in the lateral direction D3. In other words, the volume change portion 13 expands in a direction perpendicular to the fiber axis direction D1. A part of the skeletal structure 12 moves in a direction perpendicular to the fiber axis direction D1 in cooperation with the volume change portion 13 as the volume change portion 13 expands. The other part of the skeletal structure 12 moves in a direction that causes the volume change portion 13 to contract in the fiber axis direction D1. In this way, the volume change portion 13 does not expand isotropically, but contracts in one direction and expands in the other direction. That is, the volume change of the volume change portion 13 has anisotropy.
[0024] Incidentally, in order to increase the output of the actuator 1, for example, to make the actuator 1 contract more when it acts to apply a tensile force to the outside, it is necessary to use a material that has both the property of large strain caused by the input of external energy and the property of a high Young's modulus. However, generally, a material with a high Young's modulus has small strain. On the other hand, a material with a large strain has a low Young's modulus. For this reason, there have been no materials that have both properties in the past.
[0025] In contrast, by using a material having unit structures 10 for actuator 1, the Young's modulus of actuator 1 can be made higher than when actuator 1 is made only of the material that constitutes volume change portion 13.
[0026] Furthermore, when the actuator 1 is made only of the material that constitutes the skeletal structure 12, the amount of volume change when external energy is input is small, and the strain (i.e., the amount of deformation) generated in the actuator 1 is small. When the actuator 1 is made only of the material that constitutes the volume change section 13, the actuator 1 expands isotropically when external energy is input, and therefore the strain generated in the actuator 1 is small.
[0027] In contrast, in a material having unit structures 10, the volume of volume-changing portion 13 increases when external energy is input to volume-changing portion 13. The increase in the volume of volume-changing portion 13 causes skeletal structure portion 12 to deform so that accommodation portion 11 contracts in one direction and accommodation portion 11 expands in the other direction. This makes it possible to increase the strain of actuator 1 that occurs when external energy is input, compared to when actuator 1 is made only of the material that makes up skeletal structure portion 12 and when actuator 1 is made only of the material that makes up volume-changing portion 13.
[0028] In this way, it is possible to provide the actuator 1 with both a property of large distortion caused by the input of external energy and a property of high Young's modulus, thereby enabling the actuator 1 to have high output.
[0029] In the actuator 1, the contraction operation of the housing portion 11 in one direction can be used as the output of the actuator 1. However, without being limited to this, the expansion operation of the housing portion 11 in the other direction can also be used as the output of the actuator 1.
[0030] Next, a fiber material of PA12 (i.e., polyamide 12) that embodies the above material design will be described. This fiber material is produced by stretching the fiber in the manufacturing process of the PA12 fiber material, as described later. PA12 is a polyamide-based crystalline polymer material having a crystalline portion and an amorphous portion. Note that a polymer material is a polymeric organic compound. In addition to PA12, polyamide-based crystalline polymer materials include PA6 (i.e., polyamide 6) and PA66 (i.e., polyamide 66).
[0031] A fiber material made of a polyamide-based crystalline polymer material produced by fiber drawing (hereinafter, this fiber material will be referred to as a polyamide-based fiber material) has a bulk structure 20 shown in FIG.
[0032] Specifically, the polyamide fiber material has a plurality of crystalline portions 21, a plurality of tie molecules 22, and a plurality of amorphous portions 23, as shown in FIG. 3. Each of the plurality of crystalline portions 21 is a portion in which polymer chains are regularly arranged. Specifically, each of the plurality of crystalline portions 21 is a portion of a lamellar crystal. Each of the plurality of tie molecules 22 is a portion in which a polymer chain extends so as to connect each of the plurality of crystalline portions 21 to each other. The plurality of crystalline portions 21 and the plurality of tie molecules 22 form a skeletal structure surrounding each of the plurality of accommodation portions 24. Each of the plurality of amorphous portions 23 is a portion in which polymer chains are irregularly arranged. Each of the plurality of amorphous portions 23 is accommodated in each of the plurality of accommodation portions 24. That is, each of the plurality of amorphous portions 23 is confined in a portion surrounded by the plurality of crystalline portions 21 and the plurality of tie molecules 22.
[0033] The bulk structure 20 shown in FIG. 3 includes a unit structure 20A shown in FIG. 4, that is, a crystalline portion 21, a tie molecule 22, and an amorphous portion 23. As shown in FIG. 4, the crystalline portions 21 and the tie molecules 22 form a skeletal structure surrounding one accommodation portion 24. One of the amorphous portions 23 is accommodated in the accommodation portion 24. Therefore, one of the amorphous portions 23 corresponds to the volume change portion 13 of the unit structure 10 in FIG. 2. The portion of the crystalline portions 21 and the tie molecules 22 surrounding the one volume change portion 13 corresponds to the skeletal structure portion 12 of the unit structure 10 in FIG. 2.
[0034] 3 and 4, the first direction D2 and the second direction D3 are perpendicular to each other. The first direction D2 is a direction along the fiber axis direction D1. The unit structures 20A adjacent to each other in the second direction D3 are arranged with their positions in the first direction D2 shifted.
[0035] 3, the tie molecules 22 include a plurality of first tie molecules 221 extending in a first direction D2 and a plurality of second tie molecules 222 extending in the first direction D2. The first tie molecules 221 and the second tie molecules 222 are alternately arranged in a second direction D3.
[0036] A first space B1 is formed between one of the second tie molecules 222 and one of the first tie molecules 221a located adjacent to the one of the second tie molecules 222 on one side in the second direction D3. A second space B2 is formed between the one of the second tie molecules 222 and one of the first tie molecules 221b located adjacent to the one of the second tie molecules 222 on the other side in the second direction D3.
[0037] The multiple crystalline portions 21 include multiple first crystalline portions 21a provided in the first space B1. The multiple amorphous portions 23 include multiple first amorphous portions 23a provided in the first space B1. The multiple first crystalline portions 21a and the multiple first amorphous portions 23a are alternately provided in the first space B1 in the first direction D2.
[0038] The multiple crystalline portions 21 include multiple second crystalline portions 21b provided in the second space B2. The multiple amorphous portions 23 include multiple second amorphous portions 23b provided in the second space B2. The multiple second crystalline portions 21b and the multiple second amorphous portions 23b are alternately provided in the second space B2 in the first direction D2.
[0039] One of the first crystal portions 21a of the first space B1 faces one of the second amorphous portions 23b of the second space B2 in the second direction D3. That is, when one first crystal portion 21a is projected onto one second amorphous portion 23b in the second direction D3, the projected one first crystal portion 21a overlaps one second amorphous portion 23b. Also, one of the second crystal portions 21b of the second space B2 faces one of the first amorphous portions 23a of the first space B1 in the second direction D3. That is, when one second crystal portion 21b is projected onto one first amorphous portion 23a in the second direction D3, the projected one second crystal portion 21b overlaps one first amorphous portion 23a.
[0040] In this way, the position of one of the plurality of first crystal portions 21a in the first direction D2 is different from the position of one of the plurality of second crystal portions 21b in the first direction D2. The position of one of the plurality of first amorphous portions 23a in the first direction D2 is different from the position of one of the plurality of second amorphous portions 23b in the first direction D2. That is, the second crystal portion 21b is provided at a position in the second space B2 that is the same as the position of the first amorphous portion 23a in the first direction D2 in the first space B1.
[0041] The length of each of the plurality of amorphous portions 23 in the first direction D2 is longer than the length of each of the plurality of crystalline portions 21 in the first direction D2. Therefore, each of the plurality of tie molecules 22 includes a crystal linking portion 22A that is located between the first crystalline portion 21a and the second crystalline portion 21b that are in a positional relationship in which the distance in the first direction D2 is the shortest among the plurality of crystalline portions 21, and that links the first crystalline portion 21a and the second crystalline portion 21b. The crystal linking portion 22A is adjacent to both the first amorphous portion 23a and the second amorphous portion 23b in the second direction D3. The crystal linking portion 22A is inclined with respect to the first direction D2, but may be parallel to the first direction D2.
[0042] When the volume of the amorphous portion 23 expands, the outer peripheral surface of the amorphous portion 23 expanded in the second direction D3 pushes the inner peripheral surface of the tie molecule 22 in the same direction as the expansion direction. The expansion direction is the second direction D3. As the pushed tie molecule 22 deforms, the crystalline portion 21 forming a skeletal structure together with the tie molecule 22 pushes the amorphous portion 23 in the first direction D2, causing the amorphous portion 23 to contract in the first direction D2.
[0043] As shown in FIG. 4, when a cross section of the bulk structure 20 is cut so as to include the extension direction of the tie molecules 22, the cross-sectional shape of one storage section 24 is octagonal. In one storage section 24, the maximum width LD2 of the storage section 24 in the first direction D2 is longer than the maximum width LD3 of the storage section 24 in the second direction D3. The first direction D2 is the longitudinal direction of one storage section 24. The first direction D2 corresponds to one direction of the storage section 11 in FIG. 2. The second direction D3 is the lateral direction of one storage section 24. The second direction D3 corresponds to the other direction of the storage section 11 in FIG. 2.
[0044] The amorphous portions 23 are formed of randomly entangled polymer chains. These polymer chains extend generally in a first direction D2. That is, the extension direction of the polymer chains of the amorphous portions 23 is along the fiber axis direction D1. Therefore, when the overall volume of each of the plurality of amorphous portions 23 increases, each of the plurality of amorphous portions 23 shrinks in the first direction D2, and the actuator 1 having the bulk structure 20 shrinks in the fiber axis direction D1.
[0045] When the actuator 1 is heated and thermal energy is input to the amorphous portion 23, the overall volume of the amorphous portion 23 increases. When the actuator 1 is cooled and thermal energy is released from the amorphous portion 23, the overall volume of the amorphous portion 23 decreases. In other words, the input of heat and the change in volume are reversible.
[0046] The actuator 1 shrinks in the fiber axis direction D1 due to heating. The left side of FIG. 5 shows a unit structure 20A when the volume of the amorphous portion 23 is small. That is, the left side of FIG. 5 shows a unit structure 20A when the actuator 1 is not heated. This state is a natural state in which the amorphous portion 23 does not expand in volume. In this state, the tie molecule 22 in contact with the amorphous portion 23 does not receive a force that moves it in the expansion direction. Therefore, the angle φ of the tie molecule 22 t1 Here, as shown in FIG. 4, the length of the outer side of the crystal linking portion 22A of the tie molecule 22 is L. In this case, the length of the crystal linking portion 22A of the tie molecule 22 in the first direction D2 is Lcosφ t1 It is.
[0047] 5 shows a unit structure 20A when the volume of the amorphous portion 23 is large. In this case, the pushed tie molecule 22 is deformed with the expansion of the amorphous portion 23, and the angle φ t2 In this case, the length of the crystal linking portion 22A of the tie molecule 22 in the first direction D2 is L cosφ t2 In addition, the angle of the tie molecule is φ t1 , φ t2 is the angle that the crystal connection portion 22A forms with respect to the first direction D2.
[0048] When the total volume of the amorphous portion 23 increases, the unit structure 20A changes from the shape on the left side of Fig. 5 to the shape on the right side of Fig. 5. Then, the length in the first direction D2 of the crystal linking portion 22A of the tie molecule 22 becomes Lcosφ t1 From Lcosφ t2 5, the amorphous portion 23 contracts in the first direction D2 and expands in the second direction D3. In other words, the skeletal structure formed by the crystalline portion 21 and the tie molecules 22 is deformed so that the accommodation portion 24 contracts in the first direction D2 and expands in the other direction. The first direction D2 corresponds to one direction, and the second direction D3 corresponds to the other direction. In this way, the unit structure 20A imparts anisotropy to the volume change of the amorphous portion 23.
[0049] Furthermore, when the overall volume of the amorphous portion 23 decreases, the unit structure 20A changes from the shape on the right side of FIG. 5 to the shape on the left side of FIG.
[0050] It is known that fiber materials made of general crystalline polymer materials have a structure in which crystalline and amorphous parts are alternately connected, and it has been generally believed that the thermal shrinkage of fiber materials made of crystalline polymer materials is due to the entropy elasticity of the amorphous parts.
[0051] However, in polyamide fiber materials, the phenomenon caused by entropy elasticity may not be observed. Specifically, as shown in Figure 6, when tension is applied to polyamide fiber materials in the fiber axis direction, the amount of shrinkage (i.e., the linear expansion coefficient) does not increase, and as shown in Figure 7, the Young's modulus of the amorphous part differs greatly from that of the fiber material. The circles in Figure 6 indicate the measured linear expansion coefficient. The dashed straight line in Figure 6 indicates the predicted linear expansion coefficient due to entropy elasticity. The diameter of the sample used in the measurement in Figure 6 is 0.37 mm.
[0052] The shrinkage of polyamide fiber materials can be explained by the fact that the phenomenon caused by entropy elasticity is not observed if it is considered that the shrinkage is caused by the unit structure 20A shown in FIG. 4, which gives anisotropy to the volume change of the amorphous portion 23. That is, as shown in FIG. 5, the angle φ of the tie molecule 22 is changed by the volume change of the encapsulated amorphous portion 23. t1 , φ t2 A change in the elasticity of the fiber material causes anisotropy in the volume change of the bulk structure 20. In this case, the contraction of the polyamide fiber material is caused by the expansion of the free volume, not by entropy elasticity. Therefore, as shown in FIG. 6, the amount of contraction of the fiber material when tension is applied does not change even if the magnitude of the tension applied is changed. In addition, the Young's modulus of the polyamide fiber material depends on the Young's modulus of the tie molecules 22, not the amorphous portion 23. Therefore, as shown in FIG. 7, the Young's modulus of the PA6 fiber material is a value between the Young's modulus of the crystalline portion 21 and the Young's modulus of the amorphous portion 23.
[0053] Next, the basis for the fact that the polyamide fiber material has unit structure 20A will be described. The fact that the polyamide fiber material has unit structure 20A is proven by the fact that the calculated value of the linear expansion coefficient of the polyamide fiber material by geometric calculation of unit structure 20A is the same as or close to the actual measured value of the linear expansion coefficient of the polyamide fiber material.
[0054] The linear expansion coefficient of the polyamide fiber material is calculated using the following formulas 1, 2, and 3. Formulas 1, 2, and 3 are derived by analysis based on a model of the unit structure 20A.
[0055]
number
[0056]
number
[0057]
number
[0058] Linear expansion coefficient α of amorphous part 23 a As shown in FIG. 9, can be obtained by extrapolating the relationship between the degree of crystallinity and the linear expansion coefficient. In FIG. 9, the measured values of the linear expansion coefficient of PA6 with different degrees of crystallinity are plotted. From these plots, the relationship between the degree of crystallinity and the linear expansion coefficient can be obtained. From this relationship, the linear expansion coefficient when the degree of crystallinity is 0% can be calculated. The calculated linear expansion coefficient of the amorphous portion 23 of PA6 is 2.064×10 -4 / K.
[0059] Angle φ of tie molecule 22 t is determined from the results of measurements using small angle X-ray scattering. The angle φ of the tie molecule 22 of PA6 t was below 30 degrees.
[0060] The aspect ratio of the crystal portion 21 is determined from the results of measurement by wide-angle X-ray scattering. The aspect ratio of the crystal portion 21 of PA6 was 1.83.
[0061] Crystallinity X c is obtained from the results of measurement by DSC (i.e., differential scanning calorimetry). Specifically, the crystallinity degree X is calculated using the following formula for calculating the crystallinity, the measured value of the heat of fusion, and the heat of fusion of a 100% crystalline body. c The heat of fusion of a 100% crystalline body is determined by measured values or literature values.
[0062] Crystallinity = (measured heat of fusion / heat of fusion of 100% crystalline body) x 100 The measured heat of fusion of PA6 was 60.9 mJ / mg. According to data from TA Instruments, the heat of fusion of 100% crystalline PA6 is 230 mJ / mg. c was 26.5%.
[0063] When the linear expansion coefficient of PA6 was calculated using the values of these parameters, a value close to the measured value was obtained, as shown in Figure 10. The curve in Figure 10 shows the angle φ t 10 shows the calculated linear expansion coefficient of PA6 in the range of 30 degrees or less. The circles in Fig. 10 show the measured linear expansion coefficient of PA6 fiber material. From this result, it can be said that there is a high possibility that the unit structure 20A of the polyamide fiber material is correct.
[0064] Next, a method for producing the PA12 fiber material of this embodiment will be described. As shown in Fig. 11, the method for producing the PA12 fiber material includes a spinning step S1 and a drawing step S2.
[0065] In the spinning step S1, as shown in Fig. 12, pellets of polyamide 12 are introduced into an extruder 31. Inside the extruder 31, the pellets are heated to above the melting point. The heated and molten material is extruded through a nozzle and turned into fibers, and then cooled and solidified by a cooling liquid in a cooling tank 32. In this manner, undrawn fibers of polyamide 12 are formed by melt spinning.
[0066] Next, in the drawing step S2, as shown in Fig. 12, the undrawn fibers are drawn by rollers 34 and the like while being heated by heater 33 at an appropriate temperature (e.g., around 100°C) below the melting point. By appropriately setting the heating conditions and the speed of roller 34, the draw ratio with respect to the undrawn state at this time can be set to, for example, 3 times, 4 times, or 5 times. This drawing step imparts anisotropy to the shape of each of the multiple storage sections 24. The longitudinal direction of each of the multiple storage sections 24 is aligned with the fiber axis direction D1.
[0067] In this manner, a PA12 fiber material in a drawn state is produced. That is, the unit structure 20A is obtained by performing the spinning step S1 and the drawing step S2. If the drawing step S2 is not performed, the undrawn fiber may not have the unit structure 20A shown in FIG.
[0068] Next, the results of an experiment comparing a PA12 fiber material in a stretched state with PA6, PA66, and PA610 fiber materials in a stretched state will be described. As described in Patent Document 1, there are conventional actuators made of PA6 and PA66 fiber materials. Therefore, the PA6 and PA66 fiber materials used here correspond to conventional actuators.
[0069] By the above-mentioned manufacturing method, PA12 fiber material, PA6 fiber material, and PA66 fiber material were manufactured. The spinning temperature of PA12 was 210°C. The spinning temperature of PA6 was 260°C. The spinning temperature of PA66 was 285°C. The maximum stretching ratio of each of PA6 and PA66 was 4 times. Therefore, the fiber materials of PA12, PA6, and PA66 were manufactured with the same stretching ratio of 4 times. Then, the shrinkage ratio of each manufactured fiber material was measured. In the measurement of the shrinkage ratio, the shrinkage ratio of each sample was measured when each sample was heated from 30°C to 150°C without applying tension to each sample. The measurement results are shown in FIG. 13.
[0070] FIG. 13 shows the relationship between the shrinkage rate and the material density of each fiber material. This material density is the true density. The material density of each fiber material is a value measured by the measurement method specified in JIS K 7112. The straight lines in FIG. 13 are the predicted results of the shrinkage rate using a theoretical model. The Young's moduli of each fiber material, PA12, PA6, and PA66, are close to each other.
[0071] According to the theoretical model of the unit structure 20A described above, as can be seen from the formula 1, the amount of shrinkage of the fiber material is determined by the linear expansion coefficient α a That is, the larger the linear expansion coefficient of the amorphous portion 23, the larger the amount of contraction of the fiber material. The expansion of the amorphous portion 23 is due to the expansion of the free volume. Therefore, the linear expansion coefficient α ais correlated with the material density of the amorphous portion 23. That is, the smaller the material density of the amorphous portion 23, the larger the linear expansion coefficient of the amorphous portion 23. Therefore, by using a material with a low material density of the amorphous portion 23, the amount of fiber contraction can be increased. Generally, in polyamide fiber materials, the ratio of the amorphous portion 23 to the entire material is greater than the ratio of the crystalline portion 21 to the entire material. Therefore, there is a correlation between the material density of the amorphous portion 23 and the material density of the entire material. Therefore, by using a fiber material with a low material density, the amount of fiber contraction can be increased.
[0072] From the measurement results in Fig. 13, it can be seen that, as per the above theory, the PA12 fiber material, which has a lower material density than PA6 and PA66, exhibits a higher shrinkage rate than each of the PA6 and PA66 fiber materials. Therefore, as shown by the straight line in Fig. 13, it can be seen that there is a relationship in which the lower the material density of the fiber material, the greater the shrinkage rate of the fiber material.
[0073] As described in the above-mentioned Non-Patent Document 1, there is a conventional actuator made of a fiber material of PA11. The material density of PA11 is 1.03 g / cm 3 It is. The material density of PA12 is 1.01g / cm 3 , which is smaller than the material density of PA11. As described above, since there is a relationship in which the lower the material density of the fiber material, the greater the shrinkage rate of the fiber material, it is estimated that the fiber material of PA12 will exhibit a greater shrinkage rate than the fiber material of PA11.
[0074] Therefore, it is preferable to configure the actuator 1 with a fiber material of PA 12. When the actuator 1 is configured with a fiber material of PA 12, the fiber material of PA 12 may or may not contain other materials.
[0075] In the above embodiment, the fiber material of PA12 has been described as a material that embodies the above-mentioned material design. However, the material that embodies the above-mentioned material design may be a fiber material made of a polyamide resin other than PA12. Polyamide resin is a synthetic resin having an amide bond. As described above, as shown by the straight line in FIG. 13, the inventors have found that there is a relationship in which the lower the material density of the fiber material, the greater the shrinkage rate of the fiber material. For this reason, it is sufficient that the fiber material made of a polyamide resin other than PA12 has a material density smaller than that of the fiber material of the polyamide resin used in the conventional actuator. Comparing the material densities of PA6, PA66, and PA11, the material density of PA11 is the smallest. Therefore, the fiber material that constitutes the actuator 1 has a density of 0 g / cm 3 Larger, 1.03g / cm 3 A smaller polyamide resin fiber material is sufficient. This allows for higher output compared to conventional actuators made of PA6, PA66, and PA11 fiber materials.
[0076] Furthermore, the fiber material constituting the actuator 1 is not limited to being made of a single material, polyamide resin. The fiber material constituting the actuator 1 may be made of a polymer material containing polyamide resin and other polymer materials. In short, it is sufficient that the fiber material constituting the actuator 1 is made of a polymer material containing polyamide resin. When the fiber material constituting the actuator 1 is made of a polymer material containing polyamide resin and other polymer materials, it is sufficient that the density of the polymer material having the unit structure 20A shown in FIG. 4 satisfies the above-mentioned range.
[0077] At the time of filing, polymethylpentene is known as the thermoplastic resin with the smallest material density. The density of polymethylpentene is 0.83 g / cm 3For this reason, a polymer material having a low material density, such as polymethylpentene, may be mixed with the polyamide resin to set the density of the polymer material having the unit structure 20A shown in FIG. 4 to a desired value. In this case, the material density of the mixed polymer material is 0.83 g / cm 3 The minimum density of the polymeric material present at the time of filing is 0.83 g / cm 3 Considering this, when the fiber material constituting the actuator 1 is made of a single material of polyamide resin, the material density of the manufactured fiber material is 0.83 g / cm 3 It is assumed to be larger.
[0078] In addition, it is considered that the fiber material made of a polymer material other than polyamide resin and having the unit structure 20A shown in FIG. 4 has a relationship in which the lower the material density, the larger the shrinkage rate, as shown by the straight line in FIG. 13. Therefore, as long as the fiber material making up the actuator 1 has the unit structure 20A shown in FIG. 4, it is sufficient that it is made up of at least a thermoplastic crystalline or semi-crystalline polymer material other than polyamide resin. Note that the crystalline or semi-crystalline polymer material is a polymer material having a crystalline portion. In addition, the fiber material making up the actuator 1 may contain a material other than a polymer material. In addition, the shape of the material that embodies the above-mentioned material design does not have to be a fiber, and may be a shape other than a fiber, such as a film.
[0079] Second embodiment Fig. 14(a) is a side view of the actuator 1A of this embodiment before heating, Fig. 14(b) is a top view of the actuator 1A of Fig. 14(a), and Fig. 14(c) is a side view of the actuator 1A of this embodiment after heating.
[0080] 14(a), (b), and (c), the actuator 1A of this embodiment has a fiber shape. That is, the actuator 1A is made of a fiber material, and contracts in the fiber axis direction D11 of the fiber material by inputting thermal energy as external energy. As a result, a tensile force in the fiber axis direction D11 is output to the outside.
[0081] The fiber material constituting the actuator 1A includes a braided sleeve 42, a polymer material 43, and a joint portion 44. The braided sleeve 42 corresponds to the skeletal structure portion 12 in FIG. 2. The polymer material 43 corresponds to the volume change portion 13 in FIG.
[0082] The braided sleeve 42 has a cylindrical structure in which one or more fibers are combined to surround the housing portion 41, and has a structure that is more likely to expand and contract in a width direction D12 perpendicular to the fiber axis direction D11 than in the fiber axis direction D11. In the cylindrical braided sleeve 42, the width direction D12 is the radial direction of the braided sleeve 42. The housing portion 41 of the braided sleeve 42 corresponds to the housing portion 11 of the skeletal structure portion 12. As shown in Figs. 14(a) and 14(b), the braided sleeve 42 has a cylindrical shape, but it does not have to be cylindrical. Examples of fibers that constitute the braided sleeve 42 include carbon fibers, metal fibers, glass fibers, ceramic fibers, and polymer fibers.
[0083] More specifically, the braided sleeve 42 is configured such that a plurality of fibers 421 extending along the fiber axis direction D11 are bundled with spaces between them. The spacing between the fibers of the plurality of fibers 421 may be large enough so that the polymer material 43 contained therein does not flow out of the braided sleeve 42. At both ends of each of the plurality of fibers 421, each of the plurality of fibers 421 and the polymer material 43 are fixed by fixing members 45.
[0084] Even when a tensile stress is applied to the braided sleeve 42 in the fiber axis direction D11, the multiple fibers 421 constituting the braided sleeve 42 do not stretch or are difficult to stretch. Furthermore, when a tensile stress is applied to the braided sleeve 42 in the width direction D12, the multiple fibers 421 constituting the braided sleeve 42 bend. This realizes a structure that is more easily stretchable in the width direction D12 than in the fiber axis direction D11. It is preferable that the braided sleeve 42 has a structure that does not stretch in the fiber axis direction D11 with respect to the basic shape shown in FIG. 14(b) and stretches in the width direction D12 with respect to the basic shape.
[0085] The braided sleeve 42 may have other configurations. For example, the braided sleeve 42 may be formed by combining a plurality of fibers and braiding them into a mesh-like shape. Also, the braided sleeve 42 may be formed by braiding a single fiber into a mesh-like shape. In the case of a mesh-like braided configuration, the braided sleeve 42 has gaps. The size of the gaps may be such that the polymer material 43 contained therein does not flow out of the braided sleeve 42. Also, as long as the braided sleeve 42 has a structure that is more easily stretchable in the width direction D12 than in the fiber axis direction D11, the braided sleeve 42 does not have to be braided into a mesh-like shape.
[0086] The polymer material 43 is accommodated in the internal space of the braided sleeve 42. The polymer material 43 is a solid that expands isotropically when thermal energy is input when there is no constraint on its external shape. When compared under the same thermal energy input conditions, the amount of increase in volume of the polymer material 43 is greater than the amount of increase in volume of the fibers that make up the braided sleeve 42. In other words, the polymer material 43 is a material with a greater expansion coefficient than the fibers that make up the braided sleeve 42.
[0087] As the polymer material 43, an elastomer (i.e., a polymer material having elasticity) is used. The elastomer includes rubber and thermoplastic elastomer. The rubber includes silicon rubber (e.g., PDMS), natural rubber, urethane rubber, acrylic rubber, fluororubber, NBR, etc. The thermoplastic elastomer includes paraffin, EVA, etc.
[0088] The nodes 44 suppress expansion of the braided sleeve 42 in the width direction D12. The nodes 44 are thread-shaped members that are thinner than the outer shape of the braided sleeve 42. The nodes 44 are fixed around the braided sleeve 42 in an annular or spiral shape at predetermined intervals.
[0089] 14(a), for example, the node portion 44 is composed of a plurality of annular portions. Each of the plurality of annular portions goes around the periphery of the braided sleeve 42 and is disposed at intervals from each other in the fiber axis direction D11. Alternatively, the node portion 44 may be configured such that a single thread-shaped member is wound helically around the periphery of the braided sleeve 42 at a predetermined interval.
[0090] Examples of materials constituting the node portion 44 include carbon fiber, metal fiber, glass fiber, ceramic fiber, polymer fiber, etc. The material constituting the node portion 44 may be a single strand or multiple strands.
[0091] In the actuator 1A of this embodiment, the Young's modulus of the fibers constituting the braided sleeve 42 is higher than the Young's modulus of the polymer material 43. Therefore, the Young's modulus of the braided sleeve 42 is higher than the Young's modulus of the polymer material 43.
[0092] In addition, in the actuator 1A of this embodiment, when the actuator 1A is heated and thermal energy is input to the polymer material 43, the volume of the polymer material 43 increases. At this time, as can be seen by comparing FIGS. 14(a) and (c), due to the increase in the volume of the polymer material 43, the braided sleeve 42 expands in the width direction D12 and the braided sleeve 42 contracts in the fiber axis direction D11. That is, the braided sleeve 42 deforms so that the housing portion 41 contracts in the fiber axis direction D11 and expands in the width direction D12. In this embodiment, the direction along the fiber axis direction D11 corresponds to one direction. The width direction D12 corresponds to the other direction different from the one direction.
[0093] This allows the distortion of actuator 1A that occurs when thermal energy is input to be greater than when actuator 1A is made up only of the material that makes up braided sleeve 42 and when actuator 1A is made up only of polymer material 43.
[0094] In this manner, also in this embodiment, it is possible to provide the actuator 1A with both a property of large distortion caused by the input of external energy and a property of high Young's modulus, thereby enabling the actuator 1A to have high output.
[0095] As shown in Figs. 15(a), (b) and (c), the fiber material constituting the actuator 1A of this embodiment may not include the nodes 44. For the reasons described above, even if the nodes 44 are not included, the actuator 1A can have a high output. Fig. 15(a) is a side view of the actuator 1A of this embodiment that does not have nodes before heating. Fig. 15(b) is a top view of the actuator 1A of Fig. 15(a). Fig. 15(c) is a side view of the actuator 1A of this embodiment that does not have nodes after heating.
[0096] Furthermore, the actuator 1A of this embodiment has the following effects. The fiber material constituting the actuator 1A includes nodes 44. As shown in FIG. 16, when the node 44 is present, the contraction rate of the actuator 1A in the fiber axis direction D11 can be increased when the expansion coefficient of the polymer material 43 is the same, compared to when the node 44 is not present. In other words, when the volume change amount of the polymer material 43 is the same, the contraction amount of the actuator 1A in the fiber axis direction D11 can be increased. The contraction amount of the actuator 1A can be adjusted by changing the interval between the node portions 44 adjacent to each other in the fiber axis direction D11.
[0097] In the actuator 1A of this embodiment, the fibers constituting the braided sleeve 42 are preferably conductive, such as carbon fibers, metal fibers, etc., and generate heat when electricity is applied thereto. In this way, thermal energy can be input to the polymer material 43 by applying electricity to the braided sleeve 42.
[0098] Similarly, in the actuator 1A of this embodiment, it is preferable that the material constituting the nodes 44 has electrical conductivity and generates heat when electricity is applied, such as carbon fiber, metal fiber, etc. In this way, thermal energy can be input to the polymer material 43 by applying electricity to the nodes 44.
[0099] Next, an example of the actuator 1A having the above-mentioned structure will be described. The present inventors have produced the actuator 1A having the structure shown in FIG.
[0100] As shown in FIG. 17, a carbon fiber braided sleeve 42a as the braided sleeve 42 and a silicone rubber string 43a as the polymer material 43 were prepared, and the silicone rubber string 43a was inserted into the carbon fiber braided sleeve 42a. In the carbon fiber braided sleeve 42a, the multiple fibers 421 constituting the braided sleeve 42 are carbon fibers. In the carbon fiber braided sleeve 42a, the multiple fibers 421 are combined and woven into a net shape. In FIG. 17, large gaps are formed between the multiple fibers 421, but in reality, no gaps large enough to be visible are formed. The minimum inner diameter of the prepared carbon fiber braided sleeve 42a is 5 mm, and the maximum inner diameter is 8 mm. The prepared silicone rubber string 43a is a round string made of silicone rubber, with a diameter of 5 mm and a hardness of 50.
[0101] Next, as shown in FIG. 18, in order to suppress axial expansion of the silicone rubber string 43a, the axial end of the carbon fiber braided sleeve 42a and the axial end of the silicone rubber string 43a were fixed with an epoxy-based adhesive 45a as a fixing member 45.
[0102] Next, as shown in Fig. 19, a wire 44a was prepared and wound helically around the carbon fiber braided sleeve 42a. The wire 44a was then fixed to the carbon fiber braided sleeve 42a with an epoxy adhesive. This formed the joint 44. A nichrome wire with a diameter of 0.6 mm was used as the wire 44a.
[0103] In this way, an actuator 1A having the structure shown in Fig. 20 was fabricated. In the fabricated actuator 1A, a silicon rubber string 43a is disposed inside a carbon fiber braided sleeve 42a. Also, a spiral joint is formed by a wire 44a.
[0104] When the fabricated actuator 1A was heated at 200°C, the actuator 1A expanded in the width direction D12 and contracted in the fiber axis direction D11, as shown in Fig. 21. The inventors confirmed that the fabricated actuator 1A generated a stress five times or more larger than that of the actuator disclosed in the following document, which used PA6. CS Haines et al., Artificial muscles from fishing line and sewing thread. Science 343, 868-872 (2014)
[0105] (Other embodiments) The present invention is not limited to the above-mentioned embodiment, and can be appropriately modified within the scope of the claims, and includes various modified examples and modifications within the equivalent range. In addition, the above-mentioned embodiments are not unrelated to each other, and can be appropriately combined except when the combination is clearly impossible. In addition, in each of the above-mentioned embodiments, it goes without saying that the elements constituting the embodiment are not necessarily essential, except when it is particularly clearly stated that they are essential or when it is clearly considered to be essential in principle. In addition, in each of the above-mentioned embodiments, when the numbers, values, amounts, ranges, etc. of the components of the embodiment are mentioned, they are not limited to the specific numbers, except when it is particularly clearly stated that they are essential or when it is clearly limited to a specific number in principle. In addition, in each of the above-mentioned embodiments, when the material, shape, positional relationship, etc. of the components are mentioned, they are not limited to the material, shape, positional relationship, etc., except when it is particularly clearly stated or when it is limited to a specific material, shape, positional relationship, etc. in principle. [Explanation of symbols]
[0106] 10 Unit Structure 11 Storage section 12 Skeletal structure 13 Volume change section 21 Multiple crystals 22 Multiple tie molecules 23 Multiple non-contests 42 Braided Sleeve 43 Polymer materials
Claims
1. An actuator, a skeletal structure portion (12, 21, 22, 42) that forms a skeletal structure surrounding the storage portion (11, 24, 41); A volume change portion (13, 23, 43) accommodated in the accommodation portion, The volume change portion increases in volume when external energy other than mechanical energy is input from the outside, the skeletal structure portion has a higher Young's modulus than the volume change portion, When the external energy is input to the volume change portion, the volume of the volume change portion increases, and the skeletal structure is deformed such that the storage portion contracts in one direction (D2, D11) and expands in another direction (D3, D12) different from the one direction due to the increase in the volume of the volume change portion, The actuator is made of a fiber material, and outputs a tensile force in a fiber axis direction (D1, D11) of the fiber material by inputting the external energy, The one direction is a direction along the fiber axis direction, The shape of the storage portion is an anisotropic shape in which the maximum width (LD2) of the storage portion in the one direction is longer than the maximum width (LD3) of the storage portion in the other direction, The fiber material is at least composed of a polymer material having a plurality of crystalline portions (21) in which polymer chains are regularly arranged, a plurality of tie molecules (22) in which polymer chains extend so as to connect each of the plurality of crystalline portions to each other, and a plurality of amorphous portions (23) in which polymer chains are irregularly arranged; The plurality of tie molecules includes a plurality of first tie molecules (221) extending in a first direction (D2) which is the one direction, and a plurality of second tie molecules (222) extending in the first direction, each of the plurality of first tie molecules and each of the plurality of second tie molecules are alternately arranged in a second direction perpendicular to the first direction; A first space (B1) is formed between one second tie molecule of the plurality of second tie molecules and one first tie molecule (221a) located adjacent to the one second tie molecule of the plurality of first tie molecules on one side in the second direction, A second space (B2) is formed between the one second tie molecule and one first tie molecule (221b) located adjacent to the one second tie molecule on the other side in the second direction among the plurality of first tie molecules, The plurality of crystal portions include a plurality of first crystal portions (21a) provided in the first space and a plurality of second crystal portions (21b) provided in the second space, The plurality of amorphous portions include a plurality of first amorphous portions (23a) provided in the first space and a plurality of second amorphous portions (23b) provided in the second space, In the first space, the first crystal portions and the first amorphous portions are alternately provided in the first direction, In the second space, the second crystal portions and the second amorphous portions are alternately provided in the first direction, one first crystal portion of the plurality of first crystal portions in the first space faces one second amorphous portion of the plurality of second amorphous portions in the second space in the second direction, and one second crystal portion of the plurality of second crystal portions in the second space faces one first amorphous portion of the plurality of first amorphous portions in the first space in the second direction, a length of each of the plurality of amorphous portions in the first direction is longer than a length of each of the plurality of crystalline portions in the first direction, the volume changing portion is one amorphous portion among the plurality of amorphous portions, the skeletal structure portion is a portion surrounding the plurality of crystalline portions and the one amorphous portion among the plurality of tie molecules, The actuator, wherein the density of the polymer material is greater than 0 g / cm 3 and less than 1.03 g / cm 3 .
2. The actuator described in claim 1, wherein the polymeric material includes a resin having an amide bond.
3. The actuator described in claim 2, wherein the resin is polyamide 12.
4. An actuator, a skeletal structure portion (12, 21, 22, 42) that forms a skeletal structure surrounding the storage portion (11, 24, 41); A volume change portion (13, 23, 43) accommodated in the accommodation portion, The volume change portion increases in volume when external energy other than mechanical energy is input from the outside, the skeletal structure portion has a higher Young's modulus than the volume change portion, When the external energy is input to the volume change portion, the volume of the volume change portion increases, and the skeletal structure is deformed such that the storage portion contracts in one direction (D2, D11) and expands in another direction (D3, D12) different from the one direction due to the increase in the volume of the volume change portion, The actuator is made of a fiber material, and outputs a tensile force in a fiber axis direction (D1, D11) of the fiber material by inputting the external energy, The one direction is a direction along the fiber axis direction, the skeletal structure is a braided sleeve (42) having a cylindrical structure surrounding the storage portion by combining one or more fibers and having a structure that is more easily stretchable in a width direction (D12) perpendicular to the fiber axis direction than in the fiber axis direction, the volume change portion is a solid polymer material (43) that expands isotropically when thermal energy is input as the external energy when there is no constraint on its external shape; When the thermal energy is input to the polymer material, the volume of the polymer material increases, and the increase in the volume of the volume change portion causes the storage portion to shrink in the fiber axis direction and the braided sleeve to deform so that the storage portion expands in the width direction, The one or more fibers constituting the braided sleeve generate heat when an electric current is applied thereto; The textile material has nodes (44) that restrict expansion of the braided sleeve in the width direction, The nodes have a shape thinner than the outer shape of the braided sleeve, and are fixed at predetermined intervals around the braided sleeve in a circular or spiral shape.
5. An actuator as described in claim 4, wherein the material constituting the node portion generates heat when electricity is passed through it.
Citation Information
Patent Citations
Tubular actuator
DE102011121741A1
Actuator
JP2013055877A
Coiled and non-coiled twisted nanofiber yarn torsional and tensile actuators
US9784249B2
Fiber for actuators, and actuator and fiber product using same
WO2020054633A1
